Limites da atividade do provedor: o gerenciamento de dados e a responsabilidade sobre conteúdo de terceiros - Bortali, Henrique Pivato (2020)
This study aims to clarify and analyse, in a critical and objective way, about the responsibilities of the Internet Service Provider, for the content posted by third party, and your responsibility for data management available on your platforms. There are subspecies of service providers, subdivided into practical aspects of connection and application. Taking into account as online application platforms, content providers, it becomes interesting to analyze the field of accountability for the material in question, issues that show direct reflections on the balance between freedom of expression and prior censorship, carried out through of content filters. Using this idealization, the folowing study was developed, analysing the Internet Service Provider itself, and the limits of its blame for content’s posted by third party in their web sites. Along with these issues and overcoming the understandings on the providers' accountability regime with regard to content promoted by third parties, a study will be made on the data management promoted by these providers on their platforms and the aspects of their accountability arising from these situations. It will take into account the aspects introduced by the Internet era, cyberspace and the analysis of the General Data Protection Law (LGPD), an extremely current topic in the Brazilian legal scene